Spatial variation of clouding / rainfall over southeast Indian peninsula and adjoining Bay of Bengal associated with active and dry spells of northeast monsoon as derived from INSAT OLR data - AMUDHA, B.; RAJ , Y. E. A.; ASOKAN, R. (MAUSAM, 2016)
South Peninsular India (SPI) benefits largely from the rainfall (RF) realised during the North East Monsoon (NEM) season that prevails from October to December spilling over to January in some of the years. Salient aspects of clouding / RF over SPI associated with 13 NEM seasons from 2000-01 to 2012-13 have been analysed using estimates of Outgoing Long wave Radiation (OLR) at 1° × 1° resolution derived from the radiance observations in the infra-red channel onboard the geostationary operational Indian satellite (INSAT) radiometers. OLR is considered as a proxy indicator for convective activity with the value of 230 Wm-2 as the threshold for RF occurrence. Year-to-year mean OLR patterns of the NEM season along with the latitudinal and longitudinal variabilities were analysed for dry, light and active phases of NEM. Based on rigorous analysis of INSAT OLR data for the above 13 years, it has been shown that during the active phase of NEM, Coastal Tamil Nadu (CTN) receives more RF while over BoB the RF is lower and decreases sharply over interior Tamil Nadu. This is a reiteration of a similar result from an earlier study based on 3 years (1996-98) OLR data from polar orbiting NOAA satellites. The spatial variation in OLR over the latitudes of 10.5, 12.5 and 14.5° N along the longitudes of 75.5-85.5° E has revealed the feature that north of 10.5° N, values of OLR are higher with decrease in RF from south to north. During dry phase of NEM in December and January, higher OLR is observed over northern latitudes of BoB than southern latitudes. It has been comprehended that in the southern latitudes of BoB, where higher sea surface temperatures (SST) are prevalent, more moisture is generated and pumped in to upper levels of the atmosphere leading to lower values of OLR compared to northern latitudes.